Anaphylaxis from Wasp Stings Inducing Coronary Thrombus. (11th June 2012) - Kasim, Sazzli; AbuBakar, Rafidah; McFadden, Eugene
Abstract : Myocardial infarction as a result of wasp stings is a rare manifestation of acute coronary syndromes. It has been ascribed to kounis syndrome or allergic angina whose triggers include mast cell degranulation leading to coronary vasospasm and/or local plaque destabilisation. Its exact pathophysiology is still not clearly defined. We present a case of an acute coronary syndrome as a consequence of wasp stings and discuss its possible aetiology.